2021
DOI: 10.3390/genes12040596
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of a TMPRSS2 Variant on Severe COVID-19 Outcome in Young Males and Elderly Women

Abstract: The protease encoded by the TMPRSS2 gene facilitates viral infections and has been implicated in the pathogenesis of SARS-CoV-2. We analyzed the TMPRSS2 sequence and correlated the protein variants with the clinical features of a cohort of 1177 patients affected by COVID-19 in Italy. Nine relatively common variants (allele frequency > 0.01) and six missense variants which may affect the protease activity according to PolyPhen-2 in HumVar-trained mode were identified. Among them, p.V197M (p.Val197Met) (rs123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 47 publications
2
41
1
2
Order By: Relevance
“…Finally, there is some evidence that genetic polymorphisms may impact the risk for infection by SARS-CoV-2 through viral entry including ACE2 and TMPRSS2 [ 22 , 23 ]. Several studies have utilized a target gene approach to identify functional variants of these proteins associated with COVID-19 disease and severity.…”
Section: Genome-wide Association Studies Of Severe Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is some evidence that genetic polymorphisms may impact the risk for infection by SARS-CoV-2 through viral entry including ACE2 and TMPRSS2 [ 22 , 23 ]. Several studies have utilized a target gene approach to identify functional variants of these proteins associated with COVID-19 disease and severity.…”
Section: Genome-wide Association Studies Of Severe Covid-19mentioning
confidence: 99%
“…Several studies have utilized a target gene approach to identify functional variants of these proteins associated with COVID-19 disease and severity. For example, two independent studies found that the p.Val160Met variant of TMPRSS2 was associated with decreased disease severity [ 23 , 24 ] (Table 1 ). Other studies have found more frequent ACE2 allelic variability in uninfected versus SARS-CoV-2 infected individuals in Italy [ 25 ], and specific SNPs enriched in health-care works highly exposed but never infected with SARS-CoV-2 [ 26 ] (Table 1 ).…”
Section: Genome-wide Association Studies Of Severe Covid-19mentioning
confidence: 99%
“…However, the genetic variant of TMPRSS2, namely, p.V197M (p.Val197Met) (rs12329760), has a protective role in individuals against COVID-19 infection through its destructive effect on TMPRSS2 protease activity. This genetic variant is higher in individuals who have experienced milder clinical symptoms of COVID-19 (45). Therefore, it seems that by determining the polymorphisms in the TMPRSS2 gene, it is possible to identify the individual risk of infection and susceptibility to COVID-19.…”
Section: Tmprss2: Gene Polymorphisms and Their Association To Covid-19mentioning
confidence: 99%
“…It consists of a 20 aa cytoplasmic region, a 14 aa transmembrane domain, and a 120 aa extracellular SEA domain, followed by a C-terminal trypsin-like serine proteinase domain, with the characteristic catalytic triad of Ser195, His57, and Asp102 ( Fig. 3 c) [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%